Analytical study of Spiking and Its relation With Tactical Performance Of Blockers in Iraqi Volleyball Primer League (2020 – 2021) - Jawad, Abbas Fadhil; Athaab, Abaas Ali (Journal of Physical Education, 2021)
The research aimed at analyzing spike in blockers of Iraqi volleyball league clubs as well as finding a correlation relation between spiking and tactical performance of blockers. The researcher used the descriptive method on (96) Iraqi volleyball primer league club players of the season (2020 – 2021). The clubs who came first five (40) were selected and given a questioner for evaluation spiking in volleyball. Click and Scout program was used to come up with the conclusion that state a significant correlation relation between spiking and tactical performing of blocking in primer league volleyball players.